Resource rent and governance crisis in gulf of Guinea oil states: The case of Angola - Saka, Luqman; Mohd Sani, Mohd Azizuddin (Medwell Journal, 2012)

(untitled)
Studies have detailed the detrimental effects of natural resources on governance Much of the studies have gained prominence via the resource curse thesis.Though, the thesis arguments might be convincing yet there are notable exceptions of resource endowed countries that have avoided the resource curse dilemma.What then distinguishes losers from winners when it comes to resource wealth management? Is the curse that of resource or institutions? This study seeks to analysis the crisis of resource rent mis-governance in Angola, the second most important oil producing country in sub-Saharan Africa.The study looks at the mismanagement of the ever increasing rents from oil by the ruing elite and the general governance crisis in post-war Angola.